The Relationship between Type and Frequency of Complementary Feeding and Nutritional Status among Infants Aged 7–12 Months - Syam, Nurul Fitri Sugiarti; Triananinsih, Nurhidayat; Azis, Marlina; Eryanti, Rahayu (Bantayang Omni Cendekia, 2025)
Background: Nutritional status refers to the level of a person's nutritional condition which is categorized based on its type and severity, such as overweight, good nutrition, undernutrition, and malnutrition. Objective: This study aims to determine the relationship between the type and frequency of complementary feeding of BREAST MILK (MP-ASI) and the nutritional status of infants aged 7–12 months in the working area of the Mangasa Health Center. Methods: The research design used was observational with a cross-sectional approach. Results: The results showed a significant relationship between the type of MP-ASI and the nutritional status of the baby (ρ = 0.037). Most of the babies given commercial MP-ASI had normal nutritional status (61.5%), while babies given locally made MP-ASI mostly showed abnormal nutritional status (78.6%). Conclusion: It is recommended that health workers continue to improve education and counseling to mothers under five about the importance of providing proper MP-ASI, both in terms of type, frequency, and nutritional content. For mothers and families, it is expected to be more selective and active in choosing and preparing MP-ASI, by prioritizing aspects of nutritional adequacy and food safety. Local MP-ASI can still be a good choice if prepared with nutritious, clean, and suitable ingredients for the baby's needs.